Wireless Outdoor Network Planning for a Smart City Pilot - Abdah, Hadeel (2020)
This paper detail the process of radio frequency network planning and design for PASMO pilot project, an open living lab for cooperative ITS and smart cities, starting from analyzing the network and users requirements, going through choosing the appropriate technologies and equipments, and finally testing and validating the feasibility of the proposed deployment plan. Other important outcome of this work is a detailed map of the data rates and signal strength for different radio technologies, supporting the design of robust locationaware communication mechanisms.